Policing those "We All Long For": On Canadian Black Masculinities - Antwi, Phanuel (My University, 2006)
This thesis, with its three chapters covering a range of representations of police brutality, social control and Black masculinities in Canada, interrogates texts from multiple genres. My introductory chapter will contextualize the study within the field of contemporary Black Canadian literary and social texts and provides background, by mapping out, understandings of Blackness in Black Canada. My first chapter engages with national newspapers, the Globe and Mail and The Toronto Star, to name two, to examine how visual factors such as the juxtaposition of headlines, photo captions, and cutlines, the nature and quality of images, and the position of stories in the paper and on the page provide visual factors that shape media messages, which in tum shape the public understanding about Black men. Continuing my analysis of the "discursive reproduction of racism" (van Dijk 221), chapter two focuses on Dionne Brand's 2005 novel What We All Long For and Austin Clark's short story "Sometimes A Motherless Child" to address the dehumanizing abuses that encodes the Black male body during episodes of police brutality, and address the attitudes that develop about Black men in the imaginations and consciouness of many Canadians. Shifting from literal and popular texts to film, chapter three frames a reading of Charles Officer's Short Hymn, Silent War to address the trickling effects of gun violence and Black masculinities on African-Canadian women. I introduce the term conjoined subjectivities to suggest that gun violence and Black masculinities do not only affects Black men but Black women as well, thereby highlight the collective damage of these violence on Black communities. With the work done here, it becomes clear to me that more work on Black masculinities needs to be done.
Keywords: English Language and Literature; English Language and Literature